The Effect of Physical Exercise on the Aerobic Ability of Sepak Takraw Players - Alfarido, Alfarido Haloho; Ibrahim, Ibrahim Wiyaka; Mawardi, Mawardi Nur; Febrindo, Febrindo Gratama Purba; Arielf, Arielf Wahyu Pratama Hutagaol; Sitorus, Wahyu (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
This study aims to investigate the effect of physical exercise on improving the aerobic ability of sepak takraw players. A total of 10 sepak takraw athletes were the study subjects, divided into two groups. The method used was a class follow-up with a pre-test and post-test design in group A, who underwent intensive physical exercise, and group B, who did not participate in intensive physical exercise. Physical exercise includes middle-distance running, interval training, and circuit training designed to increase aerobic capacity. Aerobic ability measurement is done by examining how long the athlete can play after intensive physical exercise. The results showed a significant increase in maximal scores in group A compared to group B, with group A able to play with two se without substitutions and with a non-fatigued physical condition. This shows that specially designed physical exercise positively impacts the aerobic ability of sepak takraw players. This research provides insight into the fact that a structured physical exercise program can be essential to sepak takraw training to improve athletes' aerobic performance.